A Comprehensive Review of Recent Advances in Perovskite Materials: Electrical, Dielectric, and Magnetic Properties - Faouzia Tayari; Silvia Soreto Teixeira; Manuel Pedro F. Graca; Kais Iben Nassar (Inorganics)
Perovskite materials have emerged as one of the most promising classes of compounds in recent years due to their unique combination of electrical, dielectric, and magnetic properties, which make them ideal candidates for a wide range of advanced technological applications. This comprehensive review explores the latest developments in the electrical, dielectric, and magnetic behavior of perovskites, providing an in-depth analysis of the underlying mechanisms and their potential for improving device performance. The review covers the fundamental aspects of charge transport, polarization, and magnetic interactions in perovskite structures including the impact of crystal symmetry, ion migration, and external stimuli on their properties. Moreover, it highlights the various strategies used to tailor these properties through compositional engineering, doping, and structural modifications, resulting in enhanced efficiency, stability, and multifunctionality in applications such as photovoltaics, capacitors, dielectric resonators, and spintronic devices. Additionally, the paper addresses the challenges associated with the practical implementation of perovskite materials including stability issues under harsh environmental conditions and scalability for industrial applications. The review concludes with an outlook on future directions, emphasizing the need for further research to overcome these challenges and unlock the full potential of perovskite materials in next-generation electronics, energy storage, and magnetic devices.